Into strain mapping of structural components - Birdean, Calin-Ioan; Both, Ioan; Marginean, Ioan (2022 7th International Conference on Mathematics and Computers in Sciences and Industry (MCSI), 2022)
The capacity of a steel cross-sections is determined by the maximum stresses that develop during the load application. If a connection or a cross-section with inclined walls are the research subject, the stresses have an arduous distribution. As stresses appear correlated to strains, their measurement becomes the focus point. Strain gages are inappropriate to be used due to uncertainty of the position of maximum strains and limited local information. Strains can be conveniently monitored using Digital Image Correlation for which, if the modulus of elasticity of the materials is known, the corresponding stress can be determined. Digital Image Correlation represents a technique which is influenced by the initial settings and surface preparation. Some of the impediments that can be experienced while processing the recorded images are presented from two experimental tests, i.e. (i) an in-line connection for Rectangular Hollow Section, and (ii) a custom built-up steel cross section with inclined parts of the web. The study highlights the benefits of using DIC in monitoring specific criteria i.e. separation of the elements in the connection and different plastic deformation areas in the built-up beam cross-section, respectively. Only 40% of the maximum capacity of the connection is reached for the separation serviceability criterion. More than 50% of the theoretical capacity can be attained by the hollow flange beam due to the plastic strains developed in the beam.